2011
DOI: 10.1152/ajpheart.01174.2010
|View full text |Cite
|
Sign up to set email alerts
|

A new method to study changes in microvascular blood volume in muscle and adipose tissue: real-time imaging in humans and rat

Abstract: We employed and evaluated a new application of contrast-enhanced ultrasound for real-time imaging of changes in microvascular blood volume (MBV) in tissues in females, males, and rat. Continuous real-time imaging was performed using contrast-enhanced ultrasound to quantify infused gas-filled microbubbles in the microcirculation. It was necessary to infuse microbubbles for a minimum of 5-7 min to obtain steady-state bubble concentration, a prerequisite for making comparisons between different physiological stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 37 publications
4
85
2
Order By: Relevance
“…In agreement with our previous work and the work of Sjoberg et al, we found that with an infusion of 1.2ml·min -1 of Definity microbubbles a plateau signal was achieved at approximately 6 min Sjøberg et al 2011). Based on this an infusion time of 9 min was used before the measurements of MBV were obtained.…”
Section: Measures Of Mbvsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with our previous work and the work of Sjoberg et al, we found that with an infusion of 1.2ml·min -1 of Definity microbubbles a plateau signal was achieved at approximately 6 min Sjøberg et al 2011). Based on this an infusion time of 9 min was used before the measurements of MBV were obtained.…”
Section: Measures Of Mbvsupporting
confidence: 92%
“…Here we have again shown that age-related decrements in LBF are associated with impairments in muscle MBV responses to feeding, findings that are consistent with reports of decrements in fed-state forearm MBF (inferred from indirect measurements) (Skilton et al 2005) and also the absence of increased muscle MBF in older people fed EAA and sucrose (Timmerman et al 2012). Whereas it is well established that acute bouts of exercise enhance microvascular perfusion in both human (Vincent et al 2006) and rodent muscle (Sjøberg et al 2011), the effects of an acute neutraceutical intervention (in this case cocoa flavanols) on muscle MBF in response to nutrition, have until now remained poorly defined. Here, we have shown that 350 mg cocoa flavanols improved nutrient-dependent increases in both LBF and muscle MBF in older men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this microvascular action is independent of the ability of insulin to increase net muscle flow [12], can occur as early as 15 min following insulin infusion [19] and is partly NO-dependent [16]. It should also be noted that insulin regulates blood flow to other tissues in the body, including the heart [38], skin [39], kidney [40] and adipose [41]; however, compared with skeletal muscle these tissues contribute significantly less to postprandial glucose disposal.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound is an adapted method displaying promise for quantifying cutaneous microvascular blood flow (Sjoberg et al, 2011). To date however, this method has not been utilised following cold water immersion, having only been adopted following ice application (Selkow et al, 2012).…”
Section: Haemodynamicsmentioning
confidence: 99%